Zakah as Instrument of Islamic Microfinancing Mechanism to Productive Zakah Recipients in Malaysia - Maulidizen, Ahmad (UIN Sunan Gunung Djati Bandung, 2018)
There are various forms of zakah distribution practiced by the zakah institutions. One of them is the distribution of zakah in a form of business capital given to productive zakah recipients. This form of zakah distibution is recognized as micro-finanching mechanism. Thus, this paper attempts to analyse the potensial of zakah fund as a source of Islamic mirco financing to productive zakah recipients. The analysis is devided into several parts. Firstly, this paper discusses on the rationale of zakah fund as a source of micro financing to small Muslim entrepreneurs. It is then followed by the feasibility study of zakah as a micro financing mechanism. Secondly, this paper shares the practicality analysis of the mechanism by sharing the experience of Selangor Zakat Board. In addition, it also highlights the problems and challenges of Selangor Zakat Board in performing the role of microfinance institution. Lastly, suggestion on the proper mechanism of zakah micro financing to ensure its effectiveness is given in the final part of the paper. This is to ensure that the objectives of zakah in alleviating poverty and reducing income inequality are met.